Dynamics of Nutrient Components and Microbial Communities in Substrates During the Development of the Fruiting Bodies of Volvariella volvacea - Le Wang; Qin Dong; Qian Guo; Lei Zha; Lin Yang; Changxia Yu; Yan Zhao (Journal of Fungi, 2025)
Cotton waste, a growth medium for Volvariella volvacea, has significant commercial and nutritional value. Under controlled environmental conditions, substrate nutrient composition and microorganisms affect the growth of V. volvacea. In this study, the changes in the nutrient content of the substrate at different stages of fruiting body development were compared based on an 86% waste cotton substrate, and microbial diversity was studied via 16S rRNA analysis. The results indicated that there were significant differences in nutrient content in the substrate at different stages of fruiting body development. The total contents of carbon, nitrogen, and phosphorus initially increased but then decreased due to nutrient absorption and utilization by V. volvacea. It was also found that large amounts of organic nitrogen decomposed into more readily utilizable inorganic nitrogen. The nutritional content and microbial community structure of the substrate during the egg stage significantly differed from those during the other four stages, making the egg stage the most critical period in cultivation. Through correlation analysis between nutrient content and microbial differences, it was found that differential microbial taxa (Beijerinckiaceae, Burkholderiales, Chitinophaga jiangningensis, etc.) with nitrogen fixation, denitrification, and cellulose decomposition functions were significantly related to carbon- and nitrogen-related indicators such as nitrate nitrogen, microbial biomass carbon, and alkali-hydrolyzed nitrogen. These microorganisms play important roles in determining the variation in the nutritional profile of the substrate. This study provides a theoretical basis for promoting the absorption and utilization of nutrients by V. volvacea by altering the structure of the microbial community of the growth substrate.